Strategi Supervisi Akademik dalam Meningkatkan Kinerja Guru - Zulqaidah; Lubis, Melati Br.; Nabila Zulfa; Marsyeli; Muharil; Nasution, Inom (Medan Resource Center, 2023)
The aim of this study is to understand the strategies of academic supervision to improve the quality of teacher performance. The issue addressed in this research is the management of academic supervision for enhancing teacher performance. The research method used is qualitative, with a literature review approach based on field research. The results of this study indicate that the implementation of academic supervision management to improve teacher performance is more directed towards evaluating the performance achieved by teachers. The evaluation of the academic supervision program includes aspects such as teacher guidance, professional training and development, teacher performance appraisal, and monitoring of the 8 national education standards. Strategies employed to improve teacher performance include discipline training, serving as role models for teachers and students, organizing seminars and training sessions, collaborating with other educational institutions, inviting experts, providing opportunities for peer supervision among teachers, and optimizing educational facilities and equipment.